Technological disruptions reshaping management education: a qualitative study of stakeholder perspectives. (21st January 2021) - Gupta, Jaya; Mitra, Baishali; Garg, Kapil
The technological revolution has disrupted the business ecosystem. This calls for a paradigm shift in the essential skill-set of managers. Management education, therefore needs to transform itself to remain pertinent to the changing context. It is important to identify the management skills required of future managers and systematic reforms needed to imbibe them. In the present phenomenological qualitative study, management students, faculty, recruiters and practicing managers, the key stakeholder's, recommend the most desirable skills of business management graduates, five years into the future and also propose changes in pedagogy, course content and assessment in line with these. The data is gathered using semi-structured interviews with open-ended questions designed to answer the research questions. The results suggest that the pedagogical practices and curricula of Business Schools needs to be redesigned. The conceptual model proposed portrays the contemporary management education system comprising of a set of re-imagined curricula, pedagogy and evaluation method, which are relevant for the futuristic industry.